Alita : battle angel [videorecording (DVD)] - Salazar, Rosa, 1985-; Waltz, Christoph, 1956-; Connelly, Jennifer; Ali, Mahershala, 1974-; Kishiro, Yukito (Twentieth Century Fox Home Entertainment, 2019)
When Alita awakens with no memory in a future world she does not recognize, she is taken in by Ido, a compassionate doctor who realizes that somewhere in this abandoned cyborg shell is the heart and soul of a young woman. Ido also tries to shield Alita from her mysterious history while her street-smart new friend Hugo offers instead to help trigger her memories. But it is when the deadly and corrupt forces that run the city come after Alita that she discovers a clue to her past.